2021
DOI: 10.1017/ice.2020.1405
|View full text |Cite
|
Sign up to set email alerts
|

Real-time polymerase chain reaction (PCR) cycle threshold and Clostridioides difficile infection outcomes

Abstract: Objective: Clostridioides difficile infection (CDI) causes significant morbidity and mortality; however, the diagnosis of CDI remains controversial. The primary aim of our study was to evaluate the association of polymerase chain reaction (PCR) cycle threshold (Ct) values with CDI disease severity, recurrence, and mortality among adult patients with CDI. Design: Retrospective cohort study. Setting: Single tertiary-care hospital. Patients: Adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Previous data have revealed that the PCR-Ct can be used to predict the toxin status. 16,17 Although these previous data were able to establish potential threshold cutoff values, they were unable to determine an association with CDI severity or recurrence. 16,17 Our data indicate that as the PCR-Ct increases, the odds of recurrence at 30 days decreased (Table 3).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous data have revealed that the PCR-Ct can be used to predict the toxin status. 16,17 Although these previous data were able to establish potential threshold cutoff values, they were unable to determine an association with CDI severity or recurrence. 16,17 Our data indicate that as the PCR-Ct increases, the odds of recurrence at 30 days decreased (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…16,17 Although these previous data were able to establish potential threshold cutoff values, they were unable to determine an association with CDI severity or recurrence. 16,17 Our data indicate that as the PCR-Ct increases, the odds of recurrence at 30 days decreased (Table 3). A lower PCR-Ct could indicate a higher bacterial burden and thus could correlate to a higher amount of toxin production that would be detected by the toxin assay.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation